Models for long range forecast to the dust storms - J.AL-Azzawi, Fatimah (Iraqi Journal of Science, 2023)
In this research ,we will study the phenomenon of dust storms for all types(Suspended dust , rising dust , dust storm) , and its relationship with some climatevariables (Temperature , rainfall ,wind speed , Relative humidity ) throughregression models to three different locations ( Kirkuk , Rutba , Diwaniya ) almostcovering Iraq area for the period (1981 – 2012) . Time series has been addressing thephenomenon of storms and climate variables for the time period under study toattain the best models for long range forcast to the dust storms.